2020
DOI: 10.1038/s43018-020-00115-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation of acute lymphoblastic leukemia to the central nervous system microenvironment depends on stearoyl-CoA desaturase

Abstract: Metabolic reprogramming is a key hallmark of cancer, but less is known about metabolic plasticity of the same tumor at different sites. Here, we investigated the metabolic adaptation of leukemia in two different microenvironments, the bone marrow and the central nervous system (CNS). We identified a metabolic signature of fatty-acid synthesis in CNS leukemia, highlighting Stearoyl-CoA desaturase (SCD1) as a key player. In vivo SCD1 overexpression increases CNS disease, whilst genetic or pharmacological inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 65 publications
3
36
0
Order By: Relevance
“…In the de novo synthesis of unsaturated FAs, several desaturases and elongases work together and produce an array of C=C location isomers in mammalian lipidome ( 5 ). While knowledge on the exact functions of C=C location isomers is limited ( 6 ), increasing evidence suggests that alterations in the composition of C=C location isomers are highly sensitive to metabolic changes in cancer and other types of diseases ( 7 , 8 ). Thus, profiling of FAs at C=C location level is desirable for both fundamental studies and biomedical applications where perturbed lipid metabolism is of research interest.…”
mentioning
confidence: 99%
“…In the de novo synthesis of unsaturated FAs, several desaturases and elongases work together and produce an array of C=C location isomers in mammalian lipidome ( 5 ). While knowledge on the exact functions of C=C location isomers is limited ( 6 ), increasing evidence suggests that alterations in the composition of C=C location isomers are highly sensitive to metabolic changes in cancer and other types of diseases ( 7 , 8 ). Thus, profiling of FAs at C=C location level is desirable for both fundamental studies and biomedical applications where perturbed lipid metabolism is of research interest.…”
mentioning
confidence: 99%
“…Previous studies with quizartinib showed an immediate effect on the metabolism of AML cells (Gregory et al, 2016(Gregory et al, , 2018Gallipoli et al, 2018) and we confirm that this also applies to gilteritinib (Table S3). FGF2 or FL did not restore the pre-treatment metabolic phenotype, but rather revealed distinct adaptations, indicating the influence of the microenvironment on metabolism (Ye et al, 2020;Savino et al, 2020;Van Gastel et al, 2020;Forte et al, 2020) (Figure 4). FGF2 late cultures displayed altered sphingolipid metabolism, whereas FL late cultures preferentially utilized carnitine/fatty acid metabolism (Figures 4D-4I).…”
Section: Discussionmentioning
confidence: 99%
“…For example, when comparing hematological tumor cells cultured in human plasma-like medium to those cultured in conventional media like Dulbecco’s modified Eagle’s medium (DMEM) and Roswell Park Memorial Institute medium, widespread effects on cellular metabolism were observed, especially an inhibition of the de novo pyrimidine synthesis caused by high concentration of uric acid [ 43 ]. Moreover, the use of a medium mimicking metabolic availability in the cerebrospinal fluid revealed the dependency of leukemic cells on stearoyl-CoA desaturase upon cell infiltration into the cerebrospinal fluid [ 44 ], and also the activation of N -methyl-d-aspartate receptors on breast cancer cells in brain metastatic foci [ 45 ]. Finally, in some cancer-cell types, in vitro culture using nutrient-starved medium led to the accumulation of phosphoethanolamine, which correlates with tumor growth [ 46 ].…”
Section: Cancer Cell Adaptation To Tumor Microenvironmentsmentioning
confidence: 99%